Hypermethylation of APC2 Is a Predictive Epigenetic Biomarker for Chinese Colorectal Cancer. (29th October 2018) - He, Yuan; Sun, Li-Yue; Wang, Jing; Gong, Rui; Shao, Qiong; Zhang, Zi-Chen; Ye, Zu-Lu; Wang, Hai-Yun; Xu, Rui-Hua; Shao, Jian-Yong
Abstract : Objective . To investigate methylation of the adenomatosis polyposis coli homologue (APC2) promoter and its correlation with prognostic implications in Chinese colorectal cancer (CRC). Methods . The mRNA expression of APC2 in colorectal tissues was evaluated using the database of The Cancer Genome Atlas (TCGA). Methylation analysis of APC2 in tumor (n = 66 ) and corresponding adjacent formalin-fixed and paraffin-embedded (FFPE) tissues (n = 44 ) was performed by Sequenom EpiTYPER® and verified by cloning-based bisulfite sequencing analysis. Demethylation and retrieval of APC2 expression in cell lines HT29, HCT116, and SW480 were treated with 5-aza-2 ′ -deoxycytidine (5-AZC). Results . Analysis of TCGA showed that APC2 mRNA was significantly downregulated in primary tumors when compared to normal tissues (p < 0.05 ). APC2 methylation was upregulated (43.93% vs 7.31%, p < 0.05 ) in tumors compared to adjacent FFPE tissues. In vitro experiments demonstrated that 5-AZC downregulated the methylation of APC2 and retrieved its expression of mRNA and protein levels (p < 0.05 ). Multivariate Cox regression indicated that APC2_CPG_14 was an independent risk factor for overall survival (HR = 6.38, 95% CI: 1.59–25.64, p < 0.05 ). Conclusion . This study indicates that APC2 is hypermethylated and may be a tumorigenesis biomarker for Chinese CRC patients.